Pengaruh pertumbuhan ekonomi, pendapatan asli daerah,Dana Alokasi Umum dan dana bagi hasil terhadap kemandirian keuangan daerah pemerintah kabupaten/kota di provinsi Sumatera utara - Rapma Wati Siringo (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
ABSTRACK This study aims to examine the effect of Economic Growth, Regional Original Income, General Allocation Funds, and Revenue Sharing Funds on the Level of Regional Financial Independence in Regency/City Governments in North Sumatra Province in 2017-2021 either partially or simultaneously. The type of research used in this research is quantitative research. The sample in this study were 33 Regency/City Governments in North Sumatra Province. The type of data that will be used in this research is secondary data. The analytical method used in testing the hypothesis is Panel Data Regression. Based on the results found, it can be seen that Economic Growth and general allocation funds partially have a significant negative effect on the level of regional financial independence in the province of North Sumatra. , Regional Original Income, partially has a positive and significant influence on the Level of Regional Financial Independence of Regency/City Governments in North Sumatra. Meanwhile, the profit sharing fund has no significant effect on the level of regional financial independence. In addition to these results, other results in this study also show that simultaneously all independent variables in this study have a significant influence on the level of regional financial independence.